1991
DOI: 10.1007/bf00588045
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of limbic encephalitis

Abstract: In two patients with limbic encephalitis serial magnetic resonance (MR) imaging showed evolution of abnormal high-signal intensity in both hippocampal formations on T2-weighted images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Findings are hyperintense signals on fluid-attenuated inversion recovery and T2-weighted images in the medial temporal lobe(s), frequently without enhancement after contrast administration. [6][7][8][9] However, a normal MRI finding does not exclude PLE. 1,5 The existing literature of positron emission tomography (PET) in PLE is scarce.…”
mentioning
confidence: 99%
“…Findings are hyperintense signals on fluid-attenuated inversion recovery and T2-weighted images in the medial temporal lobe(s), frequently without enhancement after contrast administration. [6][7][8][9] However, a normal MRI finding does not exclude PLE. 1,5 The existing literature of positron emission tomography (PET) in PLE is scarce.…”
mentioning
confidence: 99%
“…Neuropathological studies have showed chronic perivascular inflammatory changes in the meninges, encephalitis with lymphocytic infiltrates of the medial temporal lobes (7,21).The histological and clinical findings were possibly due to an autoimmune phenomenon. The pathogenesis of LE-complicating malignancy is not clear.…”
Section: Discussionmentioning
confidence: 96%
“…Imaging studies has an important role in the diagnosis of LE, especially in eliminating the need for brain biopsy (11,21,22,23). CT findings are often normal, but have occasionally shown a hypodense lesion in the medial aspect of one or both temporal lobes (24).…”
Section: Discussionmentioning
confidence: 98%
“…The median age at thymoma diagnosis was 44.5 years, from age 19 to 69. The earliest case was reported by Kodama et al 7 in 1991, in which a 34-year-old woman was found to have a thymoma after presenting with AE and MG symptoms at the same time. Due to the limitation of detection technique, AE-associated antibody was not detected in this patient.…”
Section: Literature Reviewmentioning
confidence: 99%